STUDI TENTANG PELAKSANAAN PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN KEWIRAUSAHAAN DI YAYASAN PABATTA UMMI KOTA MAKASSAR - Nasrah Nasrah (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2022)
This study examines the implementation of community empowerment through entrepreneurship training at Yayassan Pabatta Ummi, Makassar City. The formulation of the problem in this is how descriptively the implementation of community empowerment through entrepreneurship training in Yayassan Pabatta Ummi, Makassar City. The purpose of the study was to describe the implementation of community empowerment through entrepreneurship training at Yayassan Pabatta Ummi, Makassar City. The results showed that community empowerment through entrepreneurship training is included in the good category. This entrepreneurship training can help participants to be able to be empowered and can get a decent livelihood for participants who take part in entrepreneurship training and other people.